Seismic Performance of a Dolphin-Type Berth Structure under Post-Fire Conditions - Abbas Rezaeian; Farhad Hosseinlou; Abdulameer Qasim Hasan; Nazar yaseen Kuioon (Journal of Hydraulic Structures)
A large number of fires occur in offshore structures as a result of oil spill or earthquake. A potential but rarely examined risk is the sequential happening of fires and earthquakes. The high ignition temperature can have serious structural influences on the seismic behavior of dolphin-type berth structure. The fire induced structural effects on the seismic performance of Dolphin structure is not well unstated, but may be critical in the occurrence of aftershocks and/or future ground excitations. Considering the irreparable consequences of reducing the seismic performance of fixed marine structures under post-fire conditions, it is vital for engineers to better understand post- fire earthquake hazards in Dolphin structure. The current manuscript presents a numerical investigation to examine the influence of post-fire conditions on the seismic behavior of dolphin-type berth structure. the main goal of this paper is to investigate the effects of fire on the seismic response of the structure. In order to better investigate the effects of temperature increase on the performance of the structure, fire is applied in the first stage near the water surface and in the second stage to the berth deck. The ABAQUS software package is utilized to model and solve the problem.